TRUTH AND RECONCILIATION COMMISSION: AN ALTERNATIVE NON-JUDICIAL SETTLEMENT OF ALLEGATIONS OF GROSS HUMAN RIGHTS VIOLATIONS - Hendra A. Ginting; Marsetio Marsetio; Hafidz Abbas; Siswo Hadi Sumantri (JURNAL PENGABDIAN MANDIRI, 2022)
Difficulties and concerns over the inability of the formal legal process to deal with past humanitarian crimes, plus the concern that this road could lead the nation back to an authoritarian regime, is a strong impetus for the need for other mechanisms, or alternative solutions, which are then generally known as "truth commissions and reconciliation”. Resolving allegations of gross human rights violations through non-judicial / non-judicial channels with the TRC mechanism can be an alternative for a country in its efforts to resolve various cases of gross human rights violations. Being able to reveal the facts or the truth and court proceedings on incidents of gross human rights violations committed by the old government regime. So that it can break the politics of impunity and usher in a new regime towards a democratic system and a rule of law as a large system for upholding human rights